In Silico Approach : Beta Glucan and AdhO36 Combinations enhance the Th1 immune response against Salmonella Typhi infection - Hidajah Rachmawati (Journal of Global Pharma Technology, 2019)
Background: Typhoid fever caused by Salmonella Typhi remains as an infectious disease that still becomes a health problem, especially in developing countries due to its fairly high morbidity. Vaccine development efforts, particularly about proteins that play a role in enhancing immunity, are adhesin protein (Protein AdhO36) and the addition of immunoadjuvant Beta Glucan that can improve the cellular immune system.Objective: This study was aimed to predict the ligand-receptor bonds (Dectin1-Beta Glucan; TLR2-Beta Glucan, TLR4-Beta Glucan) and the ligand-receptor bonds (Dectin1-AdhO36; TLR2-AdhO36, TLR4-AdhO36).Method: To determine the binding affinity of the bond between Beta-Glucan and Dectin1, TLR2, and TLR4, a molecular approach was specifically used using PyRx 0.8. Whereas to find out the interaction between Adh036 and target proteins Dectin1, TLR2, and TLR4, Patchdock software was used. The results of the interaction would be visualized using PyMol software. Amino acids involved in docking interactions were identified using KFC protein hotspots.Results and Conclusion: The result indicated  the binding affinity between receptor Dectin1-ligand Beta Glucan and Beta Glucan TLR2  was (-6.5 kcal/mol), and TLR4-Adh036 shown the highest interaction strength with global energy -1462.6.  This results shown the potential effect of AdhO36 and Beta Glucan combinations  enhanced cellular immunity against Salmonella Typhi infection.Keywords: AdhO36, Beta Glucan, TLR2, TLR 4, Dectin-1. In Silico